Asuhan Kebidanan Berkesinambungan Pada Ny.S Dengan Penerapan Teknik Rebozo Pada Persalinan (Evidence Based Case Report) - Cecilia Favian Pramuditha; Indrayani, Diyan; Chris Sriyanti; Titi Legiati (Indonesian Journal Publisher, 2025)
Background: Pregnancy and childbirth are normal processes in women, pain caused during labor can cause anxiety that can inhibit contractions and disrupt the labor process, so it requires continuous care to prepare for labor since pregnancy with one of the efforts that can be done to reduce pain during labor, namely the rebozo technique which can be used to help reduce labor pain. Objective: To provide continuous care to Mrs. S by applying the rebozo technique. Method: This study uses the Evidence Based Case Report (EBCR) method. The article search was conducted on August 15, 2024 using the Pubmed, Google Scholar and Sciene Direct databases. The keywords used are words that represent the population, namely